Update on long-term mental health outcomes in eight face transplant recipients from a single center - Huelsboemer, Lioba; Stögner, Viola A; Hosseini, Helia; Hauc, Sacha; Boroumand, Sam; Parikh, Neil; Blood, Alexa; Mookerjee, Vikram; Kauke-Navarro, Martin; Nizzi, Marie-Christine; Pomahač, Bohdan (International journal of psychiatry in medicine, 2024)
OBJECTIVE: Face transplantation is a groundbreaking and complex surgical intervention offering profound physical and psychological benefits to patients with severe facial disfigurements. This report provides an update on the long-term psychosocial outcome of eight face transplant recipients. METHOD: All transplant recipients were initially transplanted at Brigham and Women ́s Hospital (Boston, USA) between 2011 and 2020 and seen as outpatient patients at Yale New Haven Hospital (New Haven, USA). A mixed-methods approach was used to assess the psychological and social well-being of these patients. The Short-Form 12, Brief-COPE, EQ-VAS and CES-D were administered between October 2022 and October 2023. RESULTS: Older age of face transplant recipients was significantly and positively associated with better mental health and increased use of both emotional and instrumental support (Brief-COPE). The initial enhancement in patients' self-reported quality of life, as assessed by the EQVAS, declined on the EQ-VAS score at the last follow-up. Similarly, an increase in depression score was observed (CES-D score) up through the last follow-up assessment. Both of the latter results, however, did not reach statistical significance. CONCLUSIONS: These results underscore the importance of ongoing psychological support throughout the long-term journey of recovery for face transplant recipients. These findings emphasize the need for a comprehensive, patient-centered approach that also addresses the complex psychological dimensions and contributes to our understanding of the mental health dynamics involved in face transplantation, stressing the need for guidelines and continued research in this evolving field.
Keywords: dospělí; Social Support; Female; Facial Transplantation; Adult; ženské pohlaví; kvalita života; lidé; Transplant Recipients; Middle Aged; příjemce transplantátu; Male; Aged; transplantace obličeje; lidé středního věku; deprese; senioři; mužské pohlaví; Depression; Quality of Life; sociální opora; Humans